2016
DOI: 10.21037/acs.2016.05.12
|View full text |Cite
|
Sign up to set email alerts
|

The utility of the aortic dissection team: outcomes and insights after a decade of experience

Abstract: Background: Mortality rates following acute type A aortic dissection (ATAAD) repair are reduced when operations are performed by a high-volume acute aortic dissection (AAD) team, leading to efforts to centralize ATAAD care. Here, we describe our experience with ATAAD repair by our AAD team over the last 10 years, with a focus on patient selection, transfer protocols, operative approach, and volume trends over time.Methods: An AAD team was implemented at our institution in 2005, with dedicated high-volume AAD s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 39 publications
(51 reference statements)
1
34
0
Order By: Relevance
“…Lastly, the lack of significant improvement in patient outcomes over the time course of the study, and the important regional differences observed, suggest that major changes are needed to improve the care of these patients in North America. As has been previously reported by our group and others, [15][16][17][18] regionalization of care and the use of "aortic dissection teams" has clearly been shown to improve outcomes. However, in a nation as geographically large as the United States, the practicality of regionalization is challenging 19 given that data from the National Inpatient Sample database [20][21][22] suggest that only 15 to 20 centers in the United States perform more than 11 to 13 ATAD repairs per year.…”
Section: Invited Commentarysupporting
confidence: 75%
“…Lastly, the lack of significant improvement in patient outcomes over the time course of the study, and the important regional differences observed, suggest that major changes are needed to improve the care of these patients in North America. As has been previously reported by our group and others, [15][16][17][18] regionalization of care and the use of "aortic dissection teams" has clearly been shown to improve outcomes. However, in a nation as geographically large as the United States, the practicality of regionalization is challenging 19 given that data from the National Inpatient Sample database [20][21][22] suggest that only 15 to 20 centers in the United States perform more than 11 to 13 ATAD repairs per year.…”
Section: Invited Commentarysupporting
confidence: 75%
“…This program restricted all thoracic aortic surgery to be performed by cardiac surgeons specialized in aortic surgery, leading to an improvement in operative mortality. 7 Another study looking at the volume outcome relations in "all-comer" (elective þ emergent) ascending aorta/arch surgery highlighted lower midterm mortality risk for patients operated on by a high volume operator (HR: 0.67, 95% CI: 0.51-0.88). 11 Analysis of the national (U.S.) patient population by Hughes et al 12 revealed that patients operated at high volume aortic centers (30-100 cases/year) have considerably lower adjusted risk of mortality than low volume centers (< 6 cases/year) for elective ascending aortic surgery (OR: 0.42, 95% CI: 0.31-0.58).…”
Section: Discussionmentioning
confidence: 99%
“…11 Increasing evidence supports experience-outcome relationships in high-risk operations, and this relationship is also expected to be reflected in emergent aortic surgery. 7,10,12 A potential solution advocated by some centers is for referral of all aortic cases to centers specialized for aortic surgery. Volume centralization is expected to improve outcomes but this may be difficult given the emergent nature of aortic dissection and difficulty in transferring/triaging these patients in a timely fashion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These aortic pathologies are associated with high attributable mortality. The implementation of high‐volume aortic centres and structured institutional aortic teams could improve survival of patients with AAS. In this context, a regional dedicated network named S.O.S.…”
Section: Introductionmentioning
confidence: 99%